A Comparative Study on the Green Synthesis of CuO Nanoparticles from Leaf Extract Using the Combustion Method and Its Antibacterial Applications - P. Kalaivani; G. Mathubala; P. Kalaiselvi (Nanochemistry Research, 2025)
This work used leaf extracts from Ficus carica, Ficus religiosa, Annona squamosa, and Rosa rubiginosa to easily and quickly produce copper oxide nanoparticles using the combustion method, followed by their characterization and investigations on antibacterial activity against specific harmful bacteria. The nanoparticles are named copper oxide (S1, S2, S3, and S4) nanoparticles. This method is simple, safe, non-toxic, and environmentally friendly. The leaf extract functions as a reductant and stabilizing agent. From XRD analysis, the average crystallite sizes of green synthesized copper oxide (S1, S2, S3, and S4) nanoparticles were found to be 28.23 nm, 17.13 nm,  11.30 nm, and 11.31 nm, respectively. The spherical and undefinable shapes of all copper oxide nanoparticles were investigated using scanning electron microscopy, and the chemical composition of copper oxide nanoparticles was examined using EDAX spectra. FTIR spectroscopy was used to evaluate the numerous stabilizing and reducing substances found in the leaf extract that cause the formation of copper oxide (S1, S2, S3, and S4) nanoparticles. UV-visible spectroscopy was employed to evaluate the optical absorption spectra, and optical band gap of produced copper oxide nanoparticles (S1, S2, S3, and S4). This technique exhibited excellent antibacterial activity against four bacterial strains. This study effectively demonstrates the convenient utilization of leaf extracts as fuel to obtain morphologically and structurally interesting and potentially antibacterial active (S1, S2, S3, S4) CuO nanoparticles. According to the findings of this study, biosynthesized CuO nanoparticles using leaf extract could be used in biomedicine as an alternative to pharmaceutical and biological uses.